Presentation is loading. Please wait.

Presentation is loading. Please wait.

Finding the Slope of a Line From Two Points. Given the points: (3, 4) and (2, 6) Find the slope of the line. y 2 – y 1 x 2 – x 1 = x 1, y 1 x 2, y 2 6.

Similar presentations


Presentation on theme: "Finding the Slope of a Line From Two Points. Given the points: (3, 4) and (2, 6) Find the slope of the line. y 2 – y 1 x 2 – x 1 = x 1, y 1 x 2, y 2 6."— Presentation transcript:

1 Finding the Slope of a Line From Two Points

2 Given the points: (3, 4) and (2, 6) Find the slope of the line. y 2 – y 1 x 2 – x 1 = x 1, y 1 x 2, y – – == 2 -2 Problem 1

3 Given the points: (3, 0) and (6, 2) Find the slope of the line. y 2 – y 1 x 2 – x 1 = x 1, y 1 x 2, y 2 2(0) 6(3) – – = 2 3 Problem 2

4 Given the points: (0, 8) and (-3, 10) Find the slope of the line. y 2 – y 1 x 2 – x 1 = x 1, y 1 x 2, y 2 10(8) -3(0) – – = 2 Problem 3

5 Given the points: (0, 9) and (4, 7) Find the slope of the line. y 2 – y 1 x 2 – x 1 = x 1, y 1 x 2, y 2 7(9) 4(0) – – == 4 -½-½ Problem 4

6 Given the points: (3, -2) and (1, 2) Find the slope of the line. y 2 – y 1 x 2 – x 1 = x 1, y 1 x 2, y 2 2(-2) 1(3) – – == 4 -2 Problem 5

7 Given the points: (-2, 3) and (3, -6) Find the slope of the line. y 2 – y 1 x 2 – x 1 = x 1, y 1 x 2, y 2 -6(3) 3(-2) – – = -9 5 Problem 6

8 Given the points: (-1, 0) and (-3, -6) Find the slope of the line. y 2 – y 1 x 2 – x 1 = x 1, y 1 x 2, y 2 -6 (0) -3(-1) – – == Problem 7

9 Given the points: (0, 0) and (-4, -8) Find the slope of the line. y 2 – y 1 x 2 – x 1 = x 1, y 1 x 2, y 2 -8(0) -4(0) – – 2 -5 == Problem 8 5

10 Slope of Vertical and Horizontal Lines

11 y 2 – y 1 x 2 – x 1 = -4 (-4) -3(5) – – == 0 -8 zero Problem 9 5 Given the points: (5, -4) and (-3, -4) x 1, y 1 x 2, y 2

12 Given the points: (-4, -3) and (-4, 2) y 2 – y 1 x 2 – x 1 = 2 (-3) -4(-4) – – == 5 0 Undefined Problem 10 5 x 1, y 1 x 2, y 2


Download ppt "Finding the Slope of a Line From Two Points. Given the points: (3, 4) and (2, 6) Find the slope of the line. y 2 – y 1 x 2 – x 1 = x 1, y 1 x 2, y 2 6."

Similar presentations


Ads by Google